A systematic revision of the genus Juga from fresh waters of the Pacific Northwest, USA (Cerithioidea, Semisulcospiridae) - Strong, Ellen E.; Garner, Jeffrey T.; Johnson, Paul D.; Whelan, Nathan V. (European Journal of Taxonomy, 2022)
Juga is a genus of freshwater snails distributed from northern Washington to central California. The taxonomy and classification of the genus has a long and complex history, driven mainly by the features of their highly variable shells. The number of recognized species has fluctuated from 9 to 11; however, it has been claimed that the actual diversity may be three times that number. We here present a systematic revision using a recently published molecular phylogeny as a framework, which supported the interpretation that there are only nine valid species. Comprehensive review of type material and original descriptions for all available species-group names indicates that almost all species previously considered valid were para- or polyphyletic grades of organization in shell morphology. Most species previously suggested to be putatively new were confirmed to be morphological variants of species already described. Species accounts include complete synonymies and partial chresonymies; the shells and radulae are illustrated and described. Lectotypes are designated for Melania plicifera Lea, 1838, M. silicula Gould, 1847, and M. rudens Reeve, 1860. Three species, Juga caerulea sp. nov., J. canella sp. nov., and J. douglasi sp. nov., are described as new and one species is excluded from the genus. The subgenera Calibasis D.W. Taylor, 1966 and Idabasis D.W. Taylor, 1966 are synonymized with Juga.